CEMIP (HYBID, KIAA1199): structure, function and expression in health and disease: viewpoint - Spataro, Sofia; Guerra, Concetta; Cavalli, Andrea; Sgrignani, Jacopo; Sleeman, Jonathan P.; Poulain, Lina; Boland, Andreas; Scapozza, Leonardo; Moll, Solange; Prunotto, Marco (The FEBS journal, 2023)
CEMIP (cell migration-inducing protein), also known as KIAA1199 or HYBID, is a protein involved in the depolymerisation of hyaluronic acid (HA), a major glycosaminoglycan component of the extracellular matrix. CEMIP was originally described in patients affected by nonsyndromic hearing loss and has subsequently been shown to play a key role in tumour initiation and progression, as well as arthritis, atherosclerosis and idiopathic pulmonary fibrosis. Despite the vast literature associating CEMIP with these diseases, its biology remains elusive. The present review article summarises all the major scientific evidence regarding its structure, function, role and expression, and attempts to cast light on a protein that modulates EMT, fibrosis and tissue inflammation, an unmet key aspect in several inflammatory disease conditions.